Knowledge and parenting patterns with toddler’s growth and development - murdiningsih murdiningsih; Nurul Komariah (Intelektual Pustaka Media Utama, 2019)
Many factors are related to the growth and development of children. The parent factors are important, such as knowledge and parenting pattern. The purpose of the study is to analyze the correlation between knowledge and parenting patterns with toddler’s growth and development in Pre-school class in urban area of Srijaya of Palembang city within year 2017. This sstudy is an observational research with a Cross-sectional study design; it was conducted in September to October 2017. This study was conducted in Pre-school class in urban area of Srijaya of Palembang city. The population was all toddlers who attended Pre-school Class in Srijaya Palembang in year 2017. Research Samples are all toddler who follow the Pre-school class in Srijaya Palembang in year 2017 that meet the criteria of inclusion and exclusion. This research using primary data. The instrument use questionaire for knowledge and collection of biodata. For parenting variables we use Parenting Style Questioner (PSQ). In growth variable we do the measurement of body weight and height, while variable of development done by using KPSP. The result is there is correlation between mother’s knowledge with child growth (p=0.047) and child development (p=0.001). There is relationship between parenting pattern with child growth (p=0.047) and child development (p=0.001). Conclusion: there is correlation between mother's knowledge with child growth and development and there is correlation between parenting pattern with growth and development of child.